Chemical leachates from car tyre granulates and PET bottles induce toxic effects on Mytilus edulis haemocytes - M. Elisabetta Michelangeli; Sicco H. Brandsma; Maria Margalef; Emelie Forsman; Sebastian Kuehr; Davide Spanu; Tânia Gomes (Environmental Chemistry and Ecotoxicology)
Plastic materials contain hazardous chemicals, including additives like flame retardants, antioxidants, stabilizers, and metals, which can leach into the environment and impact aquatic life. This study is the first to evaluate the toxicity of leachates derived from car tyre granulates (CTG) and PET bottles (PET) on haemocytes of the mussel Mytilus edulis using a flow cytometry approach close to in vitro conditions. Following 24 h exposure, CTG leachates, characterized by a complex chemical profile (13,520 features) and high metal load, reduced cell viability, metabolic activity, mitochondrial reactive oxygen species (ROS) formation, lipid peroxidation (LPO) and lysosomal content. These leachates also impaired cytoplasmatic and mitochondrial membrane potentials, increased neutral lipids and altered DNA content. PET leachates, although with fewer chemical features (5631) and metal levels, also reduced cell viability, metabolic activity, LPO, and lysosome content, while increasing cytoplasmic membrane potential, ROS levels, NL, and altering MMP and DNA content. These findings indicated that leachates from CTG and PET can impair haemocytes functions in bivalves through mechanisms such as oxidative stress, membrane depolarization, and disrupted metabolic processes, underscoring their toxic potential. This study highlighted the toxicity pathways of plastic leachates in marine organisms, linking their complex chemical composition of organic and inorganic compounds to high ecotoxicological risks in environmental conditions.